Influence of EM-preparation on agrobiological and technological indicators of grape varieties of selection by National Scientific Center «Institute of Viticulture and Wine named after V. Ye. Tairov» - Кована, О. О.; Тарасова, В. В.; Мулюкіна, Н. А. (Scientific Progress & Innovations, 2018)
The study assessed the effect of the «EM-agro» drug on productivity, namely the increase in yields to 37 %, mainly due to the increase in the weight of berries. The inoculation of microorganisms into the ecosystem and their inclusion in the microbial groups of the leaf surface of grapes contributed to the removal of phenolic and colorants, the decrease of the activity of o-diphenol oxidase in the prototype and the prevention of the oxidation of phenolic substances. The results allow us to recommend the use of EM-preparations for organic viticulture and winemaking, both in terms of improving the productivity of grapes, and in view of improving technological performance.